Polskie badania nad krajobrazem w okresie przedkomputerowym = Polish landscape research in the pre-computer period - Richling, Andrzej (Polska Asocjacja Ekologii Krajobrazu, 2014)
Before the widespread use of computers, landscape studies required much more work and time. They were characterized by a tendency to formalize and standardize the procedures. During this period, in Poland, solutions accepted and used by most researchers have been developed, also a number of basic textbooks has been published.
Summ. eng.
Bibliogr.
244 p. : il. (color.) ; 24 cm
Keywords: landscape; history; computer